Supplementation with sweet corn for weight gain in pregnant women - Siti Mudlikah; A`im Matun Nadhiroh; Pipit Festi Wiliyanarti (Medisains)
Background: Inadequate nutrient intake during pregnancy can cause insufficient weight gain, chronic energy shortage, and difficulties for both the mother and the baby. This study highlights the benefits of sweet corn supplementation in improving weight gain and nutritional condition for pregnant women, addressing nutrient deficiencies and chronic energy shortages.